Saponins from Clematis mandshurica Rupr. regulates gut microbiota and its metabolites during alleviation of collagen-induced arthritis in rats. (November 2019) - Guo, Lin-Xiu; Wang, Huai-You; Liu, Xue-Duan; Zheng, Jia-Yi; Tang, Qi; Wang, Xin-Nan; Liu, Jian-Qun; Yin, Hua-Qun; Miao, Bo; Liang, Yi-Li; Liu, Li-Fang; Xin, Gui-Zhong
Graphical abstract: Abstract: Gut microbiota and their metabolites (short-chain fatty acids, SCFAs) are associated with the pathogenesis of rheumatoid arthritis (RA). Total Clematis triterpenoid saponins (CTSs) prepared from Clematis mandshurica Rupr. possess therapeutic benefits for arthritic diseases. However, the poor pharmacokinetic properties of CTSs have obstructed the translation of these natural agents to drugs. Here, we examined the effects of CTSs on arthritis symptoms, gut microbiota and SCFAs in rats with collagen-induced arthritis (CIA). Our results showed that the arthritis index scores of CIA rats treated with CTSs were significantly lower than those of the model group. Most importantly, CTSs moderated gut microbial dysbiosis and significantly downregulated the total SCFA concentration in CIA rats. Compared to the control group, CTSs treatment have no significant side effects on the gut microbiota and SCFA metabolism in normal rats. Two differential analyses (LEfSe and DESeq2) were combined to study the details of the changes in gut microbiome, and twenty-four marker taxa at the genus level were identified via a comparison among control, model and CIA rats treated with high doses of CTSs. In particular, the mostly significantly increased gram-negative (G − ) and decreased gram-positive (G + ) genera in CIA rats were well restored by CTSs. The observed SCFA concentrations demonstrated that CTSs tend to maintain the balance of the gut microbiota. The data presented herein suggest that CTSs could ameliorate arthritis-associated gut microbial dysbiosis and may be potential adjuvant drugs that could provide relief from the gastrointestinal damage caused as a side effect of commonly used drugs.